2014
DOI: 10.1111/1467-9655.12102
|View full text |Cite
|
Sign up to set email alerts
|

Journeys of patronage: moral economies of transactional sex, kinship, and female migration fromMozambique toEurope

Abstract: The article explores how young Mozambican women's migratory trajectories towards Europe are shaped by sexual relationships with older white men and obligations towards female kin. Triads of exchange between young women known as curtidoras (women enjoying life) and their partners and kin in Maputo are understood through theories of patronage and exchange moralities. Searching for respect, adventure, and consumption in the sexual economy, young women at the same time struggle to ensure their families' well‐being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…To identify emic CCMs we used UCINET software to perform a cultural consensus analysis on rating data (Borgatti S.P., 2002). Our initial eigenvalue ratio for the full sample was 1.37, with an average competence score of 0.31 suggesting that the 77 participants were drawing from more than one transactional sex CCM (Borgatti S.P., 2002; J.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify emic CCMs we used UCINET software to perform a cultural consensus analysis on rating data (Borgatti S.P., 2002). Our initial eigenvalue ratio for the full sample was 1.37, with an average competence score of 0.31 suggesting that the 77 participants were drawing from more than one transactional sex CCM (Borgatti S.P., 2002; J.…”
Section: Resultsmentioning
confidence: 99%
“…While the act of receiving goods from a sexual partner does not pose health risks in itself, transactional relationships are likely to reflect strong gender and economic power imbalances, making it difficult for women to negotiate condom use or sexual encounters (Dunkle et al, 2004a). Transactional sex may also hurt or help a woman’s social standing, as these relationships exist within a network of social and financial obligations (Cole, 2004; Groes-Green, 2013, 2014; Stoebenau et al, 2013; Stoebenau et al, 2011; Swidler & Watkins, 2007; Wamoyi et al, 2011; Wamoyi et al, 2010). Peers or family may encourage women to charm their partners for more gifts and financial support, and those who receive nothing in exchange for sex can be mocked as “prostitutes” (Wamoyi et al, 2011, p.9) who have devalued themselves or failed to support their family (Groes-Green, 2013, 2014; Wamoyi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, multiple studies have shown that migrants do not send money to all categories of kin but rather carefully choose who can be entrusted with remittances—a consideration often based on the strength of emotional ties, trust, the burden of obligation, as well as gender and kinship ideologies in question (Åkesson ; ; Groes‐Green ; Parreñas ). For instance, in the case of Cape Verdean (Åkesson ) and Mozambican migrants (Groes‐Green ), remittances flow with envious consistency to migrants’ parents and children, neglecting spouses or partners; Filipino female migrants open joint accounts with their daughters and give children, not their husbands, responsibility over the use of money (Parreñas ). These examples show that, rather than destroying human relationships, as the classical sociology of money would have it (Simmel ), the flow of money undermines some kinship ties but solidifies kinship relations that matter.…”
mentioning
confidence: 99%
“…Women may also move as independent migrants, often as care-workers or sex-workers, and then change to a dependant status through marriage so that the relationship between the different forms of work they perform is connected and dynamic (Kofman 2012;Lan 2008). They may shift from providing paid sex to clients in source countries to providing the same service as wives after marriage and migration (Groes-Green 2014).…”
mentioning
confidence: 99%